Impact of quarantine due to COVID-19 pandemic on health and lifestyle conditions in older adults from Centro American countries. - Neyda Ma Mendoza-Ruvalcaba; Raúl Gutiérrez-Herrera; Cecilia López; Heike Hesse; Marcio Soto-Añari; Miguel Ramos-Henderson; Juan-Carlos Cárdenas-Valverde; Loida Camargo; Nicole Caldichoury; Jorge Herrera-Pino; José Calizaya-López; Cesar Castellanos; et al. (PLoS ONE, 2022)
Background The impact of quarantine in older adults have been reported in several studies with contradictory results, reporting from negative effects to no significant outcomes or even beneficial consequences. Heterogeneity in aging plays a role in each region, the aim of this study is to analyze the impact of quarantine on health conditions (physical and mental) and lifestyle in older adults in five Centro American countries during COVID-19 pandemic. Method In this cross-sectional study, n = 712 older adults 60 years and older from Mexico, Guatemala, El Salvador, Honduras and Costa Rica were assessed by telephone. Sociodemographic data, physical and mental health, lifestyle and quarantine conditions were asked previous informed consent. Results In general, mean of days in quarantine at the moment of the study was 142 days (approximately four months and three weeks). In the analysis of the impact of the days in quarantine effects were found on the frequency of falls, functional ability in Activities of Daily Living (ADL), general cognitive function, memory, orientation, language, frequency of drinking alcohol, having a balanced diet, and being active cognitively. Some differences were found between countries. Conclusions Effects of quarantine on older adults in Centro America, requires attention of governments and healthcare to prevent long term morbidity and disability, and to promote healthy aging.